2023
DOI: 10.1061/jtepbs.teeng-7726
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Literature Review of Drone Utility in Railway Condition Monitoring

Abstract: Drones have recently become a new tool in railway inspection and monitoring (RIM) worldwide, but there is still a lack of information about the specific benefits and costs. This study conducts a systematic literature review (SLR) of the applications, opportunities, and challenges of using drones for RIM. The SLR technique yielded 47 articles filtered from 7,900 publications from 2014 to 2022. The SLR found that key motivations for using drones in RIM are to reduce costs, improve safety, save time, improve mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Procedures to handle lost-link situations are crucial to prevent drone hazards during communication losses. Assets must also incorporate drones into their safety management systems, requiring comprehensive risk evaluation and synchronization with current processes [3].…”
Section: Operational and Systems Integration Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Procedures to handle lost-link situations are crucial to prevent drone hazards during communication losses. Assets must also incorporate drones into their safety management systems, requiring comprehensive risk evaluation and synchronization with current processes [3].…”
Section: Operational and Systems Integration Challengesmentioning
confidence: 99%
“…UAVs, also known as drones, are becoming increasingly prevalent across all sectors of industry. Specifically, transportation researchers have recognized the advantages of using drones to monitor linear assets such as roadways [2], railways [3], bridges [4], and waterway utilities [5]. While the monitoring of these linear assets is well established, there has been a lack of focus on nodal assets, which are critical hubs in transportation networks where efficiency and security are paramount.…”
Section: Introductionmentioning
confidence: 99%
“…Through rigorous lab-scale experiments and extensive real-field validations, we have showcased that our approach achieves accuracy on par with conventional displacement measurement sensors, while simultaneously providing superior flexibility, reduced cost, and ease of onsite installation. Our proposed methodology holds great potential for widespread use in a variety of fields, including infrastructures, heavy industry plants, and construction sites, and is primed to make a significant impact in the expansive field of drone inspection 48,49 . Last but not least, this research holds immense potential for future autonomous inspections, reducing human intervention and improving efficiency.…”
Section: Demonstrations Of Measurement Accuracy Verificationmentioning
confidence: 99%
“…Drones also emerged as an alternative type of connected vehicle to implement systemwide multimodal infrastructure condition monitoring. Askarzadeh et al (2023) recently conducted an extensive systematic literature review of drone utility in railway condition monitoring [27]. The research found that key motivations for using drones are to reduce costs, improve safety, save time, improve mobility, increase flexibility, and enhance reliability.…”
Section: Connected Vehiclesmentioning
confidence: 99%